An investigation into resident satisfaction following the implementation of a quality assurance programme at a home for the elderly - Ellis, Susanna Louisa Hendrina Maria (Stellenbosch : Stellenbosch University, 2015)
Thesis (MCur)--Stellenbosch University, 2015.